No Significant Difference Between Suture Button and Hook Plate in Treating Acute Rockwood Type III Acromioclavicular Joint Dislocation: A Systematic Review - Xie, Chengxin; Hong, Zhenghua; Su, Yongwei; Jiang, Jiao; Luo, Hua (Arthroscopy, 2025)
To systematically review the current evidence to compare the differences in outcomes of suture button (SB) versus hook plate (HP) fixation for treating acute Rockwood type III acromioclavicular joint (ACJ) dislocation. Two reviewers independently conducted a literature search based on the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. PubMed, Embase, MEDLINE, and the Cochrane Library were systematically searched for studies comparing SB and HP in the treatment of acute Rockwood type III ACJ dislocation. Constant score, visual analog scale (VAS) score, coracoclavicular distance, operation time, and occurrence of complications were assessed. Risk of bias was assessed using The Cochrane Collaboration and Risk Of Bias In Non-randomized Studies-of Interventions tools. A total of 16 studies were included, consisting of 2 randomized controlled trials and 14 non-randomized controlled trials, with 471 patients in the SB group and 445 patients in the HP group. Among the included studies that reported patient-reported outcomes, 4 indicated significantly higher Constant scores in the SB group compared with the HP group whereas the remaining 5 found no difference between the groups. Among the 5 included studies that reported VAS scores, 2 showed statistically significant differences favoring the SB group. Among the 10 included studies that reported operation time, 3 found a shorter operation time in the SB group than in the HP group whereas 2 indicated a longer operation time for SB surgery compared with HP treatment. However, there was no statistically significant difference in coracoclavicular distance or the incidence of complications between the 2 groups. The evidence suggests no clear clinical superiority of SBs over HPs in treating acute Rockwood type III ACJ dislocations. Whereas some studies show that SB treatment may offer benefits such as higher Constant scores and lower VAS scores, most outcomes reveal no significant differences. Level Ⅲ, systematic review of Level II and Ⅲ studies.